A STUDY ON THE PRE-SERVICE ELEMENTARY MATHEMATICS TEACHERS' KNOWLEDGE ON THE CONVERGENCE AND DIVERGENCE OF SERIES IN THE CONTEXT OF THEORY AND APPLICATION - ÖZDEMİR, AHMET ŞÜKRÜ (CLAME-COMITE LATINOAMERICANO MAT EDUC, 2020)
The focus of this research is the examination of the theoretical and practical knowledge regarding the convergence and divergence of the series. In line with the research focus, it is aimed to reveal the approaches of pre-service elementary mathematics teachers on the convergence and divergence of the series with the help of the real-life problem in the context of theory and application by using the concept of harmonic series. The research carried out the qualitative research method is designed according to the case study. The data of the research have consisted of two written questions and one problem and four interview questions which were formed by the researchers and their validity and reliability were ensured. The study concluded that pre-service teachers have theoretical knowledge on the convergence of series and harmonic series. Also, their perception of series, harmonic series, convergence and divergence concepts changed in the application process and they performed different approaches in problem-solving.
Keywords: Calculus Teaching; Harmonic Series; Convergence and Divergence; Theoretical and Application